2019
DOI: 10.3892/ol.2019.11039
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of lncRNA NCK1‑AS1 distinguished patients with prostate cancer from those with benign prostatic hyperplasia

Abstract: Long non-coding (lnc)RNA NCK1 antisense RNA 1 (NCK1-AS1) has been characterized as an oncogene in cervical cancer, while its role in prostate cancer (PC) remains unknown. It was revealed in the present study that plasma NCK1-AS1 was upregulated in patients with PC when compared with patients with benign prostatic hyperplasia (BPH) and healthy controls. Upregulation of NCK1-AS1 distinguished patients with PC from patients with BPH and healthy controls. Overexpression of NCK1-AS1 led to significantly upregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Besides, NCK1-AS1 has been validated to accelerate the development of ovarian cancer [ 19 ]. In addition, its promoting role in prostate cancer [ 11 ], osteosarcoma [ 12 ], cervical cancer [ 13 ], glioma [ 14 ], etc. gives more evidence to the research value of the investigation into NCK1-AS1 in human cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, NCK1-AS1 has been validated to accelerate the development of ovarian cancer [ 19 ]. In addition, its promoting role in prostate cancer [ 11 ], osteosarcoma [ 12 ], cervical cancer [ 13 ], glioma [ 14 ], etc. gives more evidence to the research value of the investigation into NCK1-AS1 in human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NCK1-AS1 has been proved to be related with the development of different cancers, including prostate cancer [ 11 ], osteosarcoma [ 12 ], cervical cancer [ 13 ], glioma [ 14 ], etc. Intriguingly, NCK1-AS1 contributes to the development of cancers by sponging miRNAs as a competing endogenous RNA (ceRNA).…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer, a serious tumor type in men, makes no exception to the importance of lncRNA-mediated functions that relate to different hallmarks of cancer ( 11 ). Although TGF-β signaling does not seem to regulate expression of NCK1-AS1 , this lncRNA was highly expressed in prostate carcinomas and underexpressed in normal or even benign hyperplastic prostate tissue and seems to activate TGFB1 mRNA and TGF-β signaling via as yet unknown molecular mechanism ( 87 ). In contrast, the MIR100HG gene that was described in the lung cancer section was transcriptionally induced by TGF-β and formed a feed-forward signaling loop by facilitating TGFB1 mRNA stabilization and growth factor secretion by prostate cancer cells ( 46 ).…”
Section: Prostate Cancermentioning
confidence: 99%
“…12 More studies indicated that NCK1-AS1 was involved in many signaling pathways, such as CDK and TGF-β1 signaling. 12,14 By analysis of TCGA dataset, we observed the significantly upregulated NCK1-AS1 in urothelial bladder carcinoma (TCGA-BLCA, see results: http://gepia.cancer-pku.cn/detail.php?gene=NCK1-AS1). MicroRNAs (miRNAs,~20 nt) are a class of non-coding small RNAs that are highly conserved in evolution.…”
Section: Introductionmentioning
confidence: 97%